Estrategias financieras para incrementar la rentabilidad en un establecimiento de salud privado: Financial strategies to increase profitability in a private healthcare facility - Español, Español (2025)
The research aims to evaluate the liquidity and profitability of the Adventist Clinic FADBA in Brazil, through the review of its financial statements for the periods 2021 to 2023. Ruiz (2022) mentions that the incorporation of new technologies and process optimization are elements that strengthen the growth of organizations and make them sustainable. A quantitative, descriptive, non-experimental method was used, which allowed for an analysis of the financial situation. The results were measured through the Wilcoxon test, indicating significant values (p<0.05) in short- and long-term strategies, showing improvements in financial management and decision-making. The ROE shows a significant increase during the years under study regarding the efficiency of self-capital. The ROA presents improvements in the management of assets that maximize revenue. These results suggest more robust planning and permanent monitoring of indicators to measure the clinic's long-term profitability. Conclusions: Proper financial management positively influences the growth and stability of the organization.